The Framingham Risk Function Underestimated Absolute Coronary Heart Disease Risk in Czech Men - Reissigová, J.; Zvárová, J. (Methods of Information in Medicine, 2007)
Objectives: The aim was to validate the Framingham coronary heart disease (CHD) risk function with the formula by Wilson et al. (1998) in Czech men.Methods: The validation was performed within the 20-year primary prevention study of atherosclerotic risk factors (STULONG) including 1417 middle-aged men from the Czech Republic (Prague). A total of 646 men examined in 1979-1988, and followed-up for ten years, were included into the validation study. The calibration and discrimination ability of the Framingham risk function in the Czech population were explored.Results: The estimated 10-year risk of CHD by the Framingham risk function was 12.8% in 646 men, significantly higher than the observed risk (16.4 %), p = 0.013. The trend in the 10-year incidence of CHD was significantly increasing with quintiles of the estimated risk, p < 0.001. After the recalibration of the Framingham risk function, there was an insignificant difference between the estimated (18.2%) and observed (16.4%) risks of CHD, p = 0.320. The Framingham risk function classified men into those with and without CHD in the 10-year period with accuracy over 60%.Conclusions: Unlike some validation studies from Western Europe, the Framingham risk function significantly underestimated the 10-year CHD risk in the Czech Republic. In agreement with these studies, the incidence of CHD was significantly increasing across quintiles of the estimated risk.
Keywords: External validation; Framingham risk function; coronary heart disease